Formação inicial de professores de ciências: reflexões a partir das abordagens das estratégias de ensino e aprendizagem em um curso de licenciatura - Viveiro, Alessandra Aparecida; Campos, Luciana Maria Lunardi [UNESP] (My University, 2014)
We developed a case study aimed to identify and to analyze how the approach to teaching and learning strategies occurs in a science teaching degree course and what are the possible influences of this formation on the pedagogical practice of these educators. The analysis focused on documents, questionnaires and interviews with lecturers and students. There is reduced diversity of strategies in the disciplines of the specific area, with prevalence of expository classes and of laboratory, and the lecturers seem to believe that a good knowledge of specific content is enough for teaching. Despite that pedagogical disciplines do explore diverse practices, many students incorporate the academic view prevailing in the course, repeating the model of their lecturers. We stress the need for initial teacher training to take into account both aspects, the domain of the specific contents and the best ways to mediate them, forming intellectuals able to discuss and to redraw their educative actions in a perspective of transformation of the reality.

Desenvolvemos um estudo de caso que teve como objetivo identificar e analisar como ocorre a abordagem de estratégias de ensino e aprendizagem em um curso de licenciatura em ciências e quais as possíveis influências dessa formação sobre a prática pedagógica dos educadores. A análise incidiu sobre documentos, questionários e entrevistas com docentes e discentes. Há reduzida diversidade de estratégias nas disciplinas de área específica, com predomínio de aulas expositivas e de laboratório, e os docentes parecem acreditar que, para lecionar, basta um bom preparo em termos de conteúdos específicos. Apesar das disciplinas pedagógicas explorarem práticas diversificadas, muitos licenciandos incorporam a visão acadêmica predominante no curso, repetindo o modelo dos professores que tiveram. Apontamos a necessidade de que a formação trabalhe tanto o domínio dos conteúdos específicos como das melhores formas de mediá-lo, formando um intelectual capaz de discutir e reelaborar suas ações educativas em uma perspectiva de transformação da realidade.
Pre-service science teacher training: reflections from the approaches to teaching and learning strategies in a degree course
Keywords: Science education; Pre-service teacher training; Teaching and learning strategies; Ensino de ciências; Formação inicial de professores; Estratégias de ensino e aprendizagem